SUCCESSFUL INTERNAL RIB FIXATION USING SHAPP PLATE IN ADULT WOMEN WITH RIB FRACTURE AND CHRONIC PAIN: A CASE REPORT - Indraharsana, Ida Bagus Yudharma; Yasa, Ketut Putu (Jurnal Mutiara Kesehatan Masyarakat, 2025)
Rib fractures are common injuries occur 10% of all traumatically injured patients. Initial management involves adequate analgesia, thoracostomy drainage if indicated, and respiratory care. Surgical rib stabilization become increasingly important but still no international clear consensus on indication is available regarding indications and patient selection. No method and/or technique was found to be superior compared to others. The aim of this study is to describe outcome of internal rib fixation using SHAPP plate. We report a 52-year-old woman, came to emergency room (ER) after motorbike accident, right chest hit handlebar. Presented with bad right chest pain and pain when inhale, VAS 7. Chest radiograph revealed fracture right posterior rib 8,9,10 medial. Chest CT showed linier fracture non displaced of right posterior rib 7. Initial treatment consists of pain management. Patient discharged after three days. Follow up at two weeks, patient still felt right chest pain when inhale and during activities with VAS 6. Second CT revealed not found fracture of right posterior rib 6-7. Patient planned to undergo internal rib fixation. Indication of surgery is prolonged and worsened pain. Internal rib fixation used SHAPP plate. Patient clinical condition significantly improved post operative with length of stay 4 days. Follow up at one month after surgery, confirmed a full return to daily activities without pain. This study reported that rib fracture treated through internal rib fixation, allows rapid recovery as well as eradicating chronic pain causes by rib fracture its self.